Analysis of adherence behaviors in adults with diabetes mellitus type 2 (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
Diabetes mellitus is a chronic disease characterized by a complex treatment. This study will analyze the contingencies that eight adults with type 2 diabetes mellitus are subjected by the conditions established by the treatment. Based on the examination of the glycated hemoglobin, participants were divided into Group A (adequate glycemic control) and Group B (poor glycemic control). The results showed that in Group A,there was a better monitoring of the guidelines passed by the team, self-control behavior and contingencies of positive reinforcement. Meanwhile, in Group B, there was a predominance of negative reinforcement contingencies and non-discrimination of private events.
Keywords: contingency analyses; diabetes; behavior